The Impact of Tourism Pollution and Entrepreneurs’ Role to Finding Sustainable Waste Management Solutions in Kuta, Seminyak, and Ubud - Shantika, Budi; Yanti, Ni Kadek Winda; Septiadji, Rudi Rindang (Politeknik Negeri Bali, 2025)
The rapid growth of tourism in Bali, one of the world's leading tourist destinations, has contributed to an escalating waste management crisis. This research aims to assess the impact of tourism-related waste generation in Kuta, Seminyak, and Ubud and evaluate the effectiveness of existing waste management policies. This study employs a qualitative research approach, focusing on waste distribution patterns and the tourism sector's contribution to plastic waste. The participants in the study include waste management authorities, tourism-related businesses, and local communities. Data were collected through interviews and field observations to identify key sources of waste and evaluate policy implementation. Data analysis was conducted using thematic analysis to identify recurring issues and challenges. The results indicate that tourism-related businesses, particularly luxury resorts and restaurants, generate over 60% of Bali's plastic waste. Despite efforts such as the 2019 plastic ban, weak enforcement, inadequate infrastructure, and inefficient waste disposal systems continue to cause pollution and landfill overflow. The study highlights critical gaps in waste collection, recycling facilities, and policy enforcement. It suggests that tech-driven waste collection services, large-scale recycling plants, and sustainable product alternatives could offer viable solutions. Additionally, implementing sustainability-focused education programs and community-based initiatives is essential for long-term waste reduction. The research implies that stricter policy enforcement, infrastructure investment, and enhanced collaboration between the government, businesses, and local communities are necessary. Future research should focus on the feasibility of waste-to-energy projects and the impact of sustainable tourism practices on waste management.